Project-Based Classroom Management Training Using Trello for Lecturers of the Nutrition Department of the Riau Ministry of Health Polytechnic - Eko Risdianto; Falinda Oktariani; Irma Susan Paramita; Yuliana Arsil; Dewi Erowati; Yola Humaroh (Aktual: Jurnal Pengabdian Kepada Masyarakat, 2023)
Current development requires lecturers to improve their abilities and skills in using technology in learning. Skills improvement can be done, including through training activities. This activity aims to train Lecturers of the Nutrition Department of the Poltekkes Kemenkes Riau in conducting project-based class management using Trello.The activity was carried out in July 2023 at the Poltekkes Kemenkes Riau with a total of 15 workshop participants who were Lecturers from the Nutrition Department, Poltekkes Kemenkes Riau. The research instrument used was a closed questionnaire with 4 answer choices. The data analysis technique used is descriptive statistical analysis. Analysis of the participants' response to the trainingrelated to the training activities that have been carried outseen from the data obtained which is processed into the form of a percentage. Percentages are obtained based on modified Likert Scale calculations. The results showed that 100% of the training participants were categorized as strongly agreeing with the statements which represented a positive response to the workshop activities. So, it can be concluded that all participants considered this workshop positive and from this workshop the Lecturer of the Department of Nutrition at the Poltekkes Kemenkes Riau gained a better understanding of how and what Lecturers should do in managing project-based classes using trello.